Identification of Livestock Development Inhibiting Factors Bali Cattle Transmigration and Local Community in Konawe District - La Ode Arsad Sani; Sutiana Sutiana; Deki Zulkarnain; Achmad Selamet Aku; La Ode Muh Munadi; Syamsuddin Syamsuddin (Budapest International Research and Critics University, 2022)
Bali cattle are an important component in the life of farmers in addition to farming or other livestock businesses. The advantages of Bali cattle can be used as labor and manure can be used as manure. This study aims to identify the inhibiting factors for the development of Bali cattle for transmigrant and local communities in Konawe Regency from June-August 2021 using a purposive sampling technique so that there are 6 villages as research samples. Each village was taken as many as 10 respondents at simple random so that a total of 60 respondents were obtained. The research results obtained were then analyzed descriptively into percentage values. The results of the analysis show that Konawe Regency in general has prospects and potential for the development of Bali cattle because of the availability of feed, livestock breeds, productive age of breeders, 66.7% male and 33.3% male workers, experience in raising livestock, and relatively livestock marketing easy but the identified inhibiting factors are limited working capital, relatively small land for farmers, relatively low formal education, the use of natural feed is still dominant (55%), livestock diseases, and limited field extension workers.